Multi-color fluorescence live-cell imaging in Dictyostelium discoideum - Hidenori Hashimura; Satoshi Kuwana; Hibiki Nakagawa; Kenichi Abe; Tomoko Adachi; Toyoko Sugita; Shoko Fujishiro; Gen Honda; Satoshi Sawai (Cell Structure and Function)
The cellular slime mold Dictyostelium discoideum, a member of the Amoebozoa, has been extensively studied in cell and developmental biology. D. discoideum is unique in that they are genetically tractable, with a wealth of data accumulated over half a century of research. Fluorescence live-cell imaging of D. discoideum has greatly facilitated studies on fundamental topics, including cytokinesis, phagocytosis, and cell migration. Additionally, its unique life cycle places Dictyostelium at the forefront of understanding aggregative multicellularity, a recurring evolutionary trait found across the Opisthokonta and Amoebozoa clades. The use of multiple fluorescent proteins (FP) and labels with separable spectral properties is critical for tracking cells in aggregates and identifying co-occurring biomolecular events and factors that underlie the dynamics of the cytoskeleton, membrane lipids, second messengers, and gene expression. However, in D. discoideum, the number of frequently used FP species is limited to two or three. In this study, we explored the use of new-generation FP for practical 4- to 5-color fluorescence imaging of D. discoideum. We showed that the yellow fluorescent protein Achilles and the red fluorescent protein mScarlet-I both yield high signals and allow sensitive detection of rapid gene induction. The color palette was further expanded to include blue (mTagBFP2 and mTurquosie2), large Stoke-shift LSSmGFP, and near-infrared (miRFP670nano3) FPs, in addition to the HaloTag ligand SaraFluor 650T. Thus, we demonstrated the feasibility of deploying 4- and 5- color imaging of D. discoideum using conventional confocal microscopy. Key words: fluorescence imaging, organelle, cytoskeleton, small GTPase, Dictyostelium